Drivers of conflict and resilience in shifting transboundary fisheries - Jacqueline M. Vogel; Catherine Longo; Jessica Spijkers; Juliano Palacios-Abrantes; Julia Mason; Colette C.C. Wabnitz; William Cheung; U. Rashid Sumaila; Gordon Munro; Sarah Glaser; Johann Bell; Yongjun Tian; et al. (Marine Policy, 2023)

Incorporating knowledge of changes in climatic, oceanographic and ecological conditions in Canadian stock assessments - Pierre Pepin; Jacquelyne King; Carrie Holt; Helen Gurney‐Smith; Nancy Shackell; Kevin Hedges; Alida Bundy (Fish and Fisheries, 2022)
Environmental impacts on fisheries are pervasive, yet methods to account for them in stock assessments and management decisions vary in rigour and quality. The prevalence and efficacy of methods to account for environmental impacts are not well documented, limiting our ability to adequately respond to future environmental and climate changes for adaptive resource management. In Canada, legislation now requires that environmental conditions are considered in the management of fish stocks, yet the current extent of implementation in assessment processes is poorly understood. We assessed the use of climate, oceanographic and ecological considerations in science advisory processes for 178 stock assessments by Fisheries and Oceans Canada. We evaluated whether these considerations were included in conceptual hypotheses about broad‐scale mechanisms, quantitative or qualitative analyses, and the development of management advice on current or future stock status. Conceptual hypotheses were included in 46% of assessments; quantitative inclusions occurred in 21% of assessments, while qualitative interpretations appeared in 31% of assessments; and 27% of assessments included climate, oceanographic and/or ecological considerations in the advice. Assessments of salmonids, invertebrates and pelagic taxa more frequently made use of environmental data than those for groundfish and elasmobranchs. Comparing our findings with assessments in other jurisdictions highlighted a gap in Canada's ability to respond to environmental changes and a need to develop integrated management approaches, such as regional ecosystem assessments and approaches that combine modelling and empirical analyses, with socio‐economic analysis within interdisciplinary teams.

Spatial Ecology of Atlantic Halibut across the Northwest Atlantic: A Recovering Species in an Era of Climate Change - Nancy L. Shackell; Jonathan A. D. Fisher; Cornelia E. den Heyer; Daniel R. Hennen; Andrew C. Seitz; Arnault Le Bris; Dominique Robert; Michael E. Kersula; Steven X. Cadrin; Richard S. McBride; Christopher H. McGuire; Tony Kess; et al. (Reviews in Fisheries Science & Aquaculture, 2022)

Challenges of Gauging the Impact of Area-Based Fishery Closures and OECMs: A Case Study Using Long-Standing Canadian Groundfish Closures - Nancy L. Shackell; David M. Keith; Heike K. Lotze (Frontiers in Marine Science, 2021)
The United Nations Convention on Biological Diversity was established in 1993. Canada is a signatory nation that has adopted, and exceeded, the UN Aichi biodiversity target to protect 10% of coastal and marine areas through marine protected areas or “other effective area-based conservation measures” (OECMs) by 2020. However, the science of OECMs as contributors to biodiversity conservation is relatively young and their definition and efficacy testing continue to evolve. Here, we examine whether areas closed to fishing on the Scotian Shelf in Atlantic Canada, where the groundfish community had collapsed in the early 1990s, have the potential to serve as OECMs for groundfish recovery. Using long-term research survey data, we show that three long-term area-based fishing fleet closures did not enhance per capita population growth rates of the majority of 24 common groundfish species. At a regional scale, 10 out of 24 species are currently at less than 50% of their pre-collapse (1979–1992) biomass, reflecting a sustained diminished productivity, even though fishing mortality has been drastically reduced through a moratorium in 1993. Additional measures are needed to protect severely depleted groundfish, especially when the causes of continued diminished productivity are still largely unresolved. The importance of OECMs as a risk-averse approach toward sustainability is globally accepted and they can be considered a tool toward the overarching UN Sustainable Development Goals (SDG-14). Our study provides further impetus toward articulating the criteria of OECMs and improving their design, monitoring, and testing, while placing OECMs within the broader context of sustainable ecosystem-based management.

Are we ready to track climate‐driven shifts in marine species across international boundaries? ‐ A global survey of scientific bottom trawl data - Aurore A. Maureaud; Romain Frelat; Laurène Pécuchet; Nancy Shackell; Bastien Mérigot; Malin L. Pinsky; Kofi Amador; Sean C. Anderson; Alexander Arkhipkin; Arnaud Auber; Iça Barri; Richard J. Bell; et al. (Global Change Biology, 2021)
Marine biota are redistributing at a rapid pace in response to climate change and shifting seascapes. While changes in fish populations and community structure threaten the sustainability of fisheries, our capacity to adapt by tracking and projecting marine species remains a challenge due to data discontinuities in biological observations, lack of data availability, and mismatch between data and real species distributions. To assess the extent of this challenge, we review the global status and accessibility of ongoing scientific bottom trawl surveys. In total, we gathered metadata for 283,925 samples from 95 surveys conducted regularly from 2001 to 2019. We identified that 59% of the metadata collected are not publicly available, highlighting that the availability of data is the most important challenge to assess species redistributions under global climate change. Given that the primary purpose of surveys is to provide independent data to inform stock assessment of commercially important populations, we further highlight that single surveys do not cover the full range of the main commercial demersal fish species. An average of 18 surveys is needed to cover at least 50% of species ranges, demonstrating the importance of combining multiple surveys to evaluate species range shifts. We assess the potential for combining surveys to track transboundary species redistributions and show that differences in sampling schemes and inconsistency in sampling can be overcome with spatio‐temporal modeling to follow species density redistributions. In light of our global assessment, we establish a framework for improving the management and conservation of transboundary and migrating marine demersal species. We provide directions to improve data availability and encourage countries to share survey data, to assess species vulnerabilities, and to support management adaptation in a time of climate‐driven ocean changes.

Changing Physical Conditions and Lower and Upper Trophic Level Responses on the US Northeast Shelf - Kevin D. Friedland; Ryan E. Morse; Nancy Shackell; Jamie C. Tam; Janelle L. Morano; John R. Moisan; Damian C. Brady (Frontiers in Marine Science, 2020)

The rise of a marine generalist predator and the fall of beta diversity - Kari E. Ellingsen; Nigel G. Yoccoz; Torkild Tveraa; Kenneth T. Frank; Edda Johannesen; Marti J. Anderson; Andrey V. Dolgov; Nancy L. Shackell (Global Change Biology, 2020)
Determining the importance of physical and biological drivers in shaping biodiversity in diverse ecosystems remains a global challenge. Advancements have been made towards this end in large marine ecosystems with several studies suggesting environmental forcing as the primary driver. However, both empirical and theoretical studies point to additional drivers of changes in diversity involving trophic interactions and, in particular, predation. Moreover, a more integrated but less common approach to the assessment of biodiversity changes involves analyses of spatial β diversity, whereas most studies to date assess only changes in species richness (α diversity). Recent research has established that when cod, a dominant generalist predator, was overfished and collapsed in a northwest Atlantic food web, spatial β diversity increased; that is, the spatial structure of the fish assemblage became increasingly heterogeneous. If cod were to recover, would this situation be reversible, given the inherent complexity and non‐linear dynamics that typify such systems? A dramatic increase of cod in an ecologically similar large marine ecosystem may provide an answer. Here we show that spatial β diversity of fish assemblages in the Barents Sea decreased with increasing cod abundance, while decadal scale changes in temperature did not play a significant role. These findings indicate a reversibility of the fish assemblage structure in response to changing levels of an apex predator and highlight the frequently overlooked importance of trophic interactions in determining large‐scale biodiversity patterns. As increased cod abundance was largely driven by changes in fisheries management, our study also shows that management policies and practices, particularly those involving apex predators, can have a strong effect in shaping spatial diversity patterns, and one should not restrict the focus to effects of climate change alone.

Climate Change Vulnerability of American Lobster Fishing Communities in Atlantic Canada - Blair J. W. Greenan; Nancy L. Shackell; Kiyomi Ferguson; Philip Greyson; Andrew Cogswell; David Brickman; Zeliang Wang; Adam Cook; Catherine E. Brennan; Vincent S. Saba (Frontiers in Marine Science, 2019)

Marine species in ambient low‐oxygen regions subject to double jeopardy impacts of climate change - Christine H. Stortini; Denis Chabot; Nancy L. Shackell (Global Change Biology, 2017)
We have learned much about the impacts of warming on the productivity and distribution of marine organisms, but less about the impact of warming combined with other environmental stressors, including oxygen depletion. Also, the combined impact of multiple environmental stressors requires evaluation at the scales most relevant to resource managers. We use the Gulf of St. Lawrence, Canada, characterized by a large permanently hypoxic zone, as a case study. Species distribution models were used to predict the impact of multiple scenarios of warming and oxygen depletion on the local density of three commercially and ecologically important species. Substantial changes are projected within 20–40 years. A eurythermal depleted species already limited to shallow, oxygen‐rich refuge habitat (Atlantic cod) may be relatively uninfluenced by oxygen depletion but increase in density within refuge areas with warming. A more stenothermal, deep‐dwelling species (Greenland halibut) is projected to lose ~55% of its high‐density areas under the combined impacts of warming and oxygen depletion. Another deep‐dwelling, more eurythermal species (Northern shrimp) would lose ~4% of its high‐density areas due to oxygen depletion alone, but these impacts may be buffered by warming, which may increase density by 8% in less hypoxic areas, but decrease density by ~20% in the warmest parts of the region. Due to local climate variability and extreme events, and that our models cannot project changes in species sensitivity to hypoxia with warming, our results should be considered conservative. We present an approach to effectively evaluate the individual and cumulative impacts of multiple environmental stressors on a species‐by‐species basis at the scales most relevant to managers. Our study may provide a basis for work in other low‐oxygen regions and should contribute to a growing literature base in climate science, which will continue to be of support for resource managers as climate change accelerates.

Ecosystem‐based fisheries management in the Northwest Atlantic - Jason S Link; Alida Bundy; William J Overholtz; Nancy Shackell; John Manderson; Daniel Duplisea; Jon Hare; Mariano Koen‐Alonso; Kevin D Friedland (Fish and Fisheries, 2011)
The northwest Atlantic has had a notable history of living marine resource (LMR) exploitation. There have been calls for evaluating and improving approaches to manage those resources as stocks have undergone sequential depletion, with some dramatic instances of stock declines. The need for more holistic ecosystem‐based approaches to manage LMRs has been increasingly recognized as part of these calls, along with the recognition that there are broader issues to consider when managing a fishery. We discuss some of the major efforts to this end which are extant among our institutions. We emphasize current initiatives to implement ecosystem‐based fisheries management in the northwest Atlantic, with a focus on how advice based on the natural sciences supports an ecosystem‐based approach. We present this information as a case study within a rich historical context of fisheries science and management.

Structure and stability in exploited marine fish communities: quantifying critical transitions - BRIAN PETRIE; KENNETH T. FRANK; NANCY L. SHACKELL; WILLIAM C. LEGGETT (Fisheries Oceanography, 2009)
Correlations between time series of the abundance of predator and prey fish species in heavily exploited western North Atlantic marine fisheries vary temporally but are generally positive in southern, warmer waters and negative in northern, colder ones. The correlations provide an index of trophic structure and dynamics. We construct a framework to quantify critical thresholds between states in which the predator–prey correlations are positive or negative. We do so by developing a quantitative model of the distribution of the correlations between predator (15 species) and prey (8 species) functional groups based on the annual predator depletion rates and bottom temperatures (or alternatively species richness). The model accounts for 58% of the variance of the correlations with a root mean square error of 0.3. This index of trophic structure indicates that warmer, species‐rich, southern fish populations resist transformation from positive to negative predator–prey correlations at exploitation rates that can be double those in the colder, relatively species‐poor, northern areas. The model can be used to set limits for exploitation rates that preserve the functional relationships between predator–prey groups in emerging fisheries, and to assess the potential for and measures required to achieve recovery of degraded fish communities.

Temporal dynamics within a contemporary latitudinal diversity gradient - Jonathan A. D. Fisher; Kenneth T. Frank; Brian Petrie; William C. Leggett; Nancy L. Shackell (Ecology Letters, 2008)
Poleward declines in species diversity [latitudinal diversity gradients (LDG)] remain among the oldest and most widespread of macroecological patterns. However, their contemporary dynamics remain largely unexplored even though changing ecological conditions, including global change, may modify LDG and their respective ecosystems. Here, we examine temporal variation within a temperate Northwest Atlantic LDG using 31 years of annual fisheries‐independent surveys and explore its dynamics in relation to a dominant climate signal [the wintertime North Atlantic Oscillation (NAO)] that varies interannually and alters the latitudinal gradient of Northwest Atlantic continental shelf bottom water temperatures. We found that the slopes of the annual LDG vary dramatically due to changes in geographic distributions of 100+ species, variations that are concealed within the cumulative, static LDG. These changes are strongly associated with changes in NAO sign and strength. This is the first illustration of temporal dynamics in a contemporary LDG and the first demonstration of the speed at which local environmental variations can alter an LDG. Our findings underscore the need to investigate factors that modify LDG separately from those that contribute to their origins.

Reconciling differences in trophic control in mid‐latitude marine ecosystems - Kenneth T. Frank; Brian Petrie; Nancy L. Shackell; Jae S. Choi (Ecology Letters, 2006)
The dependence of long‐term fishery yields on primary productivity, largely based on cross‐system comparisons and without reference to the potential dynamic character of this relationship, has long been considered strong evidence for bottom‐up control in marine systems. We examined time series of intensive empirical observations from nine heavily exploited regions in the western North Atlantic and find evidence of spatial variance of trophic control. Top‐down control dominated in northern areas, the dynamics evolved from bottom‐up to top‐down in an intermediate region, and bottom‐up control governed the southern areas. A simplified, trophic control diagram was developed accounting for top‐down and bottom‐up forcing within a larger region whose base state dynamics are bottom‐up and can accommodate time‐varying dynamics. Species diversity and ocean temperature co‐varied, being relatively high in southern areas and lower in the north, mirroring the shifting pattern of trophic control. A combination of compensatory population dynamics and accelerated demographic rates in southern areas seems to account for the greater stability of the predator species complex in this region.